Implications of the new law of financing of the group Radio Televisión Española (RTVE) - Caldevilla Domínguez, David (Estudios sobre el Mensaje Periodístico, 2012)
The new Financing Law of the Spanish Radio and Television Corporation has proved controversial since its announcement by Vice President Maria Teresa Fernandez de la Vega. The new law is a response to years of criticism from private television operators and requires the matching of European directives in the sector. The new legislation represents a watershed in the history of RTVE, with a transformation of a mixed system of an institutional and advertising financing, to one without any advertising, in line with other Western European nations, which has been well received by their public.